PENGARUH POLA ASUH KELUARGA TERHADAP KARAKTER ANAK DALAM PENDIDIKAN ISLAM DI SEKOLAH - Fathimah Az-Zahra , Siti; Pertiwi, Hana; Dzaki Abiyyu Athaullah, Muhammad; Gusmaneli, Gusmaneli (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research discusses the influence of family parenting styles on children's Islamic character in school education. Parental parenting has an important role in forming a child's character, especially in terms of Islamic religious education. Case studies in several areas show that parents' Islamic parenting styles can shape religious character in children. Parents' strategies for forming religious character in children include example, habituation, and creating conducive conditions. Factors that influence parents' parenting patterns include parents' economic status and employment, as well as parents' personalities. This research provides an overview of the importance of parenting styles in shaping children's character and strategies that can be implemented to support parents' Islamic parenting styles. The family environment has a very close relationship in shaping a child's character. Therefore, parents should be more careful in educating their children, so that children have good character. This research was carried out with the aim of scientifically analyzing the influence of parental parenting on the formation of children's character. The research method used is the descriptive verification method, namely research carried out to determine the value of the independent variable, either one or more (independent) variables without making comparisons, or connecting them with other variables.